Effect of feeding on spawning of common carp - Mishra, Ashutosh; Singh, U P (Indian Journal of Fisheries, 2011)
The present investigation was carried out in four non-drainable rectangularponds for observing maturation and spawning period of common carp. For satisfactorybreeding of fish in confined water, feeding with suitable high energydiets rich in protein was supplied. For finding gonadal maturation, gonad weight,gonado - somatic index and fertilization rates were observed. The range of gonadweight and gonado-somatic index of male and female fish were 20.93 - 45.13g and 10.92 - 12.09%, 28.95 - 60.1 g and 14.60 - 16.00% respectively. The fertilizationrate was 73.57 - 82.00%. The study indicate that spawning and fertilizationrate in common carp is affected by nutritious feeds rich in protein